The bidirectional relationship between subjective visual function and domain-specific cognition in cognitively unimpaired older adults and adults with mild cognitive impairment - Dubois, Abigail; Sergio, Jordan; Mozdbar, Sima; Price, Ashley; Stradtman, Megan; Thompson, Louisa I.; Snyder, Peter J.; Alber, Jessica (Frontiers in Aging Neuroscience, 2024)
IntroductionSubjective visual impairment (VI) is related to cognition in cognitively unimpaired (CU) older adults, mild cognitive impairment (MCI) patients, and Alzheimer’s disease (AD) patients. The utility of subjective VI as an indicator for domain-specific cognitive impairment is unknown.MethodsWe used the National Eye Institute Visual Function Questionnaire (NEI-VFQ-25 item) and a neuropsychological battery to assess the relationship between subjective VI and domain-specific cognitive performance in CU older adults (N = 58) and MCI patients (N = 16).ResultsThe CU group showed a positive relationship between subjective VI and visuospatial performance. CU older adults at high risk for AD demonstrated a unique relationship between subjective VI and attention, processing speed, and executive function. Peripheral vision was related to domain-specific performance in the patient group.DiscussionSubjective VI complaints may indicate potential for domain-specific cognitive decline in visuospatial performance, executive function, processing speed, and attention in older adults.